2011
DOI: 10.1037/a0024437
|View full text |Cite
|
Sign up to set email alerts
|

Basic emotions elicited by odors and pictures.

Abstract: The sense of olfaction is often reported to have a special relationship with emotional processing. Memories triggered by olfactory cues often have a very emotional load. On the other hand, basic negative or positive emotional states should be sufficient to cover the most significant functions of the olfactory system including ingestion, hazard avoidance, and social communication. Thus, we investigated whether different basic emotions can be evoked in healthy people through the sense of olfaction. We asked 119 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
55
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(59 citation statements)
references
References 21 publications
3
55
1
Order By: Relevance
“…As for the liking and morality judgments, previous research have shown that these could be influenced by aversive odors (Alaoui-Ismaili, Robin, Rada, Dittmar, & Vernet-Maury, 1997;Croy, Olgun, & Joraschky, 2011;Herz, Schankler, & Beland, 2004;Kirk-Smith, Van Toller, & Dodd, 1983;Reicher, Templeton, Neville, Ferrari, & Drury, 2016;Rozin & Fallon, 1987;Schnall, Haidt, Clore, & Jordan, 2008;Stevenson, 2010;Yeshurun & Sobel, 2010), but whether odor evaluative conditioning would similarly shape morality and liking judgments is unclear.…”
Section: Introductionmentioning
confidence: 99%
“…As for the liking and morality judgments, previous research have shown that these could be influenced by aversive odors (Alaoui-Ismaili, Robin, Rada, Dittmar, & Vernet-Maury, 1997;Croy, Olgun, & Joraschky, 2011;Herz, Schankler, & Beland, 2004;Kirk-Smith, Van Toller, & Dodd, 1983;Reicher, Templeton, Neville, Ferrari, & Drury, 2016;Rozin & Fallon, 1987;Schnall, Haidt, Clore, & Jordan, 2008;Stevenson, 2010;Yeshurun & Sobel, 2010), but whether odor evaluative conditioning would similarly shape morality and liking judgments is unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Although a variety of different emotion testing methods have been developed, few appear to have been critically tested as a validation process and are oftentimes hybrids of other methods. This review will investigate emotion testing methods from , Thomson et al (2010), Desmet et al (2000), and Croy et al (2011) as these are unique, published, and relatively recent methods.…”
Section: Current Emotion Testing Methodsmentioning
confidence: 99%
“…The sense of smell has long been associated with eliciting emotions (Croy et al, 2011) and as explored earlier olfaction and emotion processes occur in similar regions of the brain, including the OFC (Rolls & Grabenhorst, 2008), thus Croy et al, (2011) was interested in the elicitation of emotions by odors and pictures. Participants were asked to list odors which they thought would elicit specified emotions: happiness, anger, disgust, sadness, anxiety, and surprise.…”
Section: Eliciting Emotions With Odors and Picturesmentioning
confidence: 99%
See 2 more Smart Citations